Metabolomics and lipidomics insight into the effect of different polyamines on tomato plants under non-stress and salinity conditions. (September 2022) - Buffagni, Valentina; Zhang, Leilei; Senizza, Biancamaria; Rocchetti, Gabriele; Ferrarini, Andrea; Miras-Moreno, Begoña; Lucini, Luigi
Abstract: Polyamines (PAs) are key signaling molecules involved in plant growth and stress acclimation processes. This work investigated the effect of spermidine, spermine, and putrescine (alone and in a mixture) in tomato plants using a combined metabolomics and lipidomics approach. The experiments were carried out under non-stress and 100 mM NaCl salinity conditions. Shoot and root biomass, as well as SPAD values, were increased by the application of exogenous PAs but with differences across treatments. Similarly, root length density (F: 34, p < 0.001), average root diameter (F: 14, p < 0.001), and very fine roots (0.0–0.5 mm) increased in PA-treated plants, compared to control. Metabolomics and lipidomics indicated that, despite being salinity the hierarchically prevalent factor, the different PA treatments imposed distinct remodeling at the molecular level. Plants treated with putrescine showed the broader modulation of metabolite profile, whereas spermidine and spermine induced a comparatively milder effect. The pathway analysis from differential metabolites indicated a broad and multi-level intricate modulation of several signaling molecules together with stress-related compounds like flavonoids and alkaloids. Concerning signaling processes, the complex crosstalk between phytohormones (mainly abscisic acid, cytokinins, the ethylene precursor, and jasmonates), and the membrane lipids signaling cascade (in particular, sphingolipids as well as ceramides and other glycerophospholipids), was involved in such complex response of tomato to PAs. Interestingly, PA-specific processes could be observed, with peculiar responses under either control or salinity conditions. Graphical Abstract: ga1 Highlights: Spermine, spermidine and putrescine and the combined treatment showed specific effects on tomato plants. Polyamines triggered a multi-level intricate modulation of several signaling molecules on tomato plants. Secondary metabolism, phytohormones and lipids were strongly modulated by polyamines. Polyamines triggered different responses under salt-stress compared to non-stress conditions.